Effect of Γ-aminobutyric acid on kidney injury induced by renal ischemia-reperfusion in male and female rats: Gender-related difference - Vafapour, Marzieh (Adv Biomed Res, 2015)
BACKGROUND: The most important cause of kidney injury is renal ischemia/reperfusion injury (IRI), which is gender-related. This study was designed to investigate the protective role of Γ-aminobutyric acid (GABA (against IRI in male and female rats. MATERIALS AND METHODS: Thirty-six female and male wistar rats were assigned to six experimental groups. The IRI was induced by clamping renal vessels for 45 min then was performed reperfusion for 24 h. The group sex posed to IRI were pretreated with GABA and were compared with the control groups. RESULTS: Serum levels of creatinine and blood urea nitrogen, kidney weight, and kidney tissue damage score increased in the IRI alone groups, (P < 0.05), while GABA decreased these parameters in female significantly (P < 0.05), but not in male rats. Uterus weight decreased significantly in female rats treated with GABA. Testis weight did not alter in male rats. Serum level of nitrite and kidney level of malondialdehyde (MDA) had no significant change in both female and male rats. Kidney level of nitrite increased significantly in female rats experienced IRI and serum level of MDA increased significantly in males that were exposed to IRI (P < 0.05). CONCLUSION: GABA could ameliorate kidney injury induced by renal IRI in a gender dependent manner.